2019
DOI: 10.1002/berj.3588
|View full text |Cite
|
Sign up to set email alerts
|

Student–teacher closeness and conflict in students with and without special educational needs

Abstract: Teachers play a key role in creating effective conditions for students to succeed in school. The quality of student-teacher relationships is consistently associated with social, emotional, behavioural and academic adjustment, and this is even more relevant for students with special educational needs (SEN), considering these students' emotional, social and learning vulnerabilities. This study aimed to examine the associations between students' externalising and internalising behaviour, social skills and academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
1
14
1
Order By: Relevance
“…Research has shown that children with SEN and LD have difficulties in social skills (Freire et al, 2019;Wiener & Schneider, 2002). Compared to their classmates, children with SEN tend to have lower levels of prosocial behaviors (Dasioti & Kolaitis, 2018), are less accepted (Broomhead, 2019) and have fewer or no friends (Banks et al, 2018;Pinto et al, 2019).…”
Section: School Adjustment In Children With Sen and Ldmentioning
confidence: 99%
See 3 more Smart Citations
“…Research has shown that children with SEN and LD have difficulties in social skills (Freire et al, 2019;Wiener & Schneider, 2002). Compared to their classmates, children with SEN tend to have lower levels of prosocial behaviors (Dasioti & Kolaitis, 2018), are less accepted (Broomhead, 2019) and have fewer or no friends (Banks et al, 2018;Pinto et al, 2019).…”
Section: School Adjustment In Children With Sen and Ldmentioning
confidence: 99%
“…In addition, children with SEN present problems in terms of closeness and conflict with teachers (Freire et al, 2019) and children with LD have higher levels of dependency (Pasta et al, 2013) and greater dissatisfaction in their relationships with teachers (Murray & Greenberg, 2001) than their classmates. Children with LD tend to perceive significantly high levels of school danger (Murray & Greenberg, 2001) and in both in children with SEN and LD, the presence of internalizing and externalizing problems, such as emotional symptoms and hyperactivity, seems to be correlated with bullying victimization (Boyes et al, 2020;Dasioti & Kolaitis, 2018).…”
Section: School Adjustment In Children With Sen and Ldmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to work not only on the training of future teachers but also on training in the active teachers in conflict management, small or large, which inevitably emerge in the teacherstudent relationship, throughout their professional life. Also, the Freire et al [42] results support the importance of professional development opportunities with a focus on facilitating the relationship of teachers with students with perceived challenging behavior.…”
Section: School Conflicts Managementmentioning
confidence: 83%